Pola Interaksi Guru dengan Siswa Berbasis al Rahmah: Telaah terhadap Q.S Ali Imran: 159 dan al Kahf: 60-82 - Sutarto, Sutarto (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
Interaction Patterns of Teachers and Students Based on al Rahmah: A study of Q.S Ali Imran: 159 and al Kahf: 60-82 Teacher interaction with students is crucial in the learning process, but not all teachers can do it well. Library research with a thematic approach (maudhu’iy) aims to reveal the pattern of teacher-student interaction based on mercy based on the Koran Surat Ali Imran: 159 and al Kahf: 60-82. The research data comes from primary and secondary data, then analyzed by content analysis and comparative. The results of the study revealed that there are several basic principles contained in sura Ali Imran: 159 and surah al Kahf: 60-82 related to mercy-free interactions, namely interactions must be carried out gently, not harshly, forgive each other, based on deliberation, earnest, sincere and trustful and must be done with great affectioner, based on deliberation, and sincerely. Sincere and trustful and must be done with love